2009
DOI: 10.1080/01634370802609197
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Rural and Urban Older Adults in Iowa on Specific Markers of Successful Aging

Abstract: This study examines the differences between rural and urban older adults on level of life satisfaction and depressive symptoms, focusing on the effect of social support. Data were collected through structured interviews at senior centers and senior meal sites in eastern and southeastern Iowa. The Duke Social Support Index (DSSI), the Life Satisfaction Index-Z (LSI-Z), and the Geriatric Depression Scale 15 (GDS15) were used. Correlations (Pearson's r), independent sample t-tests, and multiple regression were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
4
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 34 publications
5
30
4
1
Order By: Relevance
“…The pattern of rural-urban differences in depression observed among older adults in China is very different from that found in other countries (e.g., Britain, Canada, Japan, Korea, Taiwan and United States) where either no significant difference (Abe, Fujise, Fukunage, Nakagawa, & Ikeda, 2012; Kim, Shin, Yoon, & Stewart, 2002; St John, Blandford, & Strain, 2006) or a rural advantage (Chiu, Chen, Huang & Mau, 2005; Evans, 2009; Friedman, Conwell, & Delavan, 2007; Kim, Stewart, Shin, Yoon, & Lee, 2004; Walters et al, 2004) has been reported. Why is the prevalence of depression higher in rural than urban older adults in China?…”
contrasting
confidence: 91%
“…The pattern of rural-urban differences in depression observed among older adults in China is very different from that found in other countries (e.g., Britain, Canada, Japan, Korea, Taiwan and United States) where either no significant difference (Abe, Fujise, Fukunage, Nakagawa, & Ikeda, 2012; Kim, Shin, Yoon, & Stewart, 2002; St John, Blandford, & Strain, 2006) or a rural advantage (Chiu, Chen, Huang & Mau, 2005; Evans, 2009; Friedman, Conwell, & Delavan, 2007; Kim, Stewart, Shin, Yoon, & Lee, 2004; Walters et al, 2004) has been reported. Why is the prevalence of depression higher in rural than urban older adults in China?…”
contrasting
confidence: 91%
“…27–28 Social support may be especially important to residents of Appalachia, where disease rates are high and strong informal social support network values are normative. 2935 In this context, researchers have suggested social support may serve as a buffer against the impact of life stressors. 27–28,36 …”
Section: Multiple Morbidity and Self-managementmentioning
confidence: 99%
“…A previous study has shown that older women that live in rural areas require more support, where in some communities they are struggling to stay living independently and sustain their well-being (34). There seem to be differences in social support, where urban older-adults tend to feel more depressed due to anonymity in cities, suggesting they are more lonely; contrary to rural older-adults who have stronger social connections that they can trust and depend on (35).…”
Section: Background (Factors Affecting Internet Usage Of Older-adults)mentioning
confidence: 99%